"Yuh Mad Man!" Lying Letters: Speculations on the Catalysts of Male Madness in Caribbean Literature - Jan Anderson (Caribbean Studies Students' Union, 2012)
Jan Anderson is invested in tracing the Trajectory Home (a working title for a collection of essays) among the African Diaspora, particularly those of Caribbean descent. The experiences and contestations over issues of belonging, citizenship, and nation building are also at the heart of Jan's work. Jan's submission has led to a focus on the recurrence of disenfranchisement as a legacy of "diaspora" and the resulting fissures in male/female relationships.